2010
DOI: 10.1007/s00455-010-9279-z
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation Program for Prosthetic Tracheojejunal Voice Production and Swallowing Function Following Circumferential Pharyngolaryngectomy and Neopharyngeal Reconstruction with a Jejunal Free Flap

Abstract: The case of a 68-year-old woman with postoperative speech and swallowing problems following a circumferential pharyngolaryngectomy and neopharyngeal reconstruction with a jejunal free flap is presented. The primary tumor was an extended papillary thyroid carcinoma (pT4N0M0). For vocal restoration, an indwelling Provox® 1 voice prosthesis was inserted secondarily. The patient received speech and swallowing therapy, including digital maneuvers at the level of the proximal (cervical) part of the jejunal graft to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Several studies have reported on the use of prosthetics for voice restoration following TPL . However, most of these were small case series or included various reconstruction methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported on the use of prosthetics for voice restoration following TPL . However, most of these were small case series or included various reconstruction methods.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported on the use of prosthetics for voice restoration following TPL. 6,7,[9][10][11] However, most of these were small case series or included various reconstruction methods. Therefore, the features and complications of an indwelling voice prosthesis in patients who undergo TPL with free jejunal reconstruction have not been established in large cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…No specific swallowing rehabilitation programmes for laryngectomized patients have been described yet, and based on careful VF-evaluation, swallowing exercises by the SLP often have to be individualized. 9 Smell/taste rehabilitation Loss of (passive) sense of smell is yet another obvious consequence of the disconnection of the upper and lower respiratory tracts, and the relevance of olfaction for taste is well known. Tracheostoma breathing precludes passage of breathing air along nasal olfactory epithelium and thus of 'registration' of odour molecules, essential for normal passive sense of smell.…”
Section: Dysphagia Rehabilitationmentioning
confidence: 99%